Topological Structures of Derivative Weighted Composition Operators on the Bergman Space - Ce-Zhong Tong; Cheng Yuan; Ze-Hua Zhou (Journal of Function Spaces)
We characterize the difference of derivative weighted composition operators on the Bergman space in the unit disk and determine when linear-fractional derivative weighted composition operators belong to the same component of the space of derivative weighted composition operators on the Bergman space under the operator norm topology.